4 - La répartition des moyens d’incitation à la production entre cultures d’exportation et cultures vivrières en Côte d’Ivoire: by René Kouassi - René Kouassi (Africa Development, 1993)
The difficulties Africa has in feeding its people , particularly its urban populations , are generally attributed to the impoverished food sectoř in agriculture. In the majority of African countries , this impoverishment is the result of the post-colonial agricultural policy that favours cash crop production to the detriment of food crop production. A case study of Côte d'Ivoire agriculture , considered to be the most efficient in sub-Saharan Africa via constant reference to the 'Ivorian Miracle ' underscores this point. Policies of agricultural pricing , crop diversification , agricultural credit and the marketing and transformation of agricultural products are primarily oriented towards cash-cropping. So too are existing structures of transportation and industrial outlets. Although there has been an increase in the volume of food crops , the increase is not proportional to population growth. Consequently there is a sizeable need to import foodstuffs to feed the growing urban population. The long-term result of these policies has been depopulation of the impoverished rural areas. All these factors point to the need for rethinking national agricultural policy. The revised policy must give equal emphasis to both sectors of agriculture so as to minimize the need for importing food and assure a more harmonious development for the rural sector.